UNJUK KERJA MOTOR BENSIN GENERATOR-SET BERBAHAN BAKAR CAMPURAN BIOETANOL NIRA TEBU - Abdi Hanra Sebayang; Aditya Pangestu; Rico Aditia Prahmana (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2022)
An increase in fuel oil consumption occurs every year, and an increase in population causes this. To overcome these problems, developed alternative fuels such as bioethanol. This research was conducted using an experimental method to analyze the performance of a single-cylinder SI motor fueled with a mixture of bioethanol. Bioethanol is produced from raw sugarcane juice through fermentation with the help of the bacterium Saccharomyces cerevisiae. The composition of the fuel mixture used is 5% bioethanol+95% Premium (Ron 88), 5% bioethanol+95% Pertalite (Ron 90) and 5% bioethanol+95% Pertamax (Ron 92), which is then analyzed for the performance of the motor gasoline generator sets. The results showed that a Premium of 240.9 W obtains the highest power of the bioethanol mixture. The specific fuel consumption was reduced, obtained for Premium of 1.417 kg/Wh, and the highest power of bioethanol mixture was obtained for Pertalite. The result shows that the highest power is 218.67 W and, the torque is 0.803 Nm. Thermal efficiency is obtained at 38.711% for Pertalite. The Pertamax bioethanol mixture has power, and torques are 220 W and 0.875 Nm, respectively. Moreover, the fuel consumption value obtained is 1.573 kg/Wh, and the mixture's thermal efficiency is 42,524%. The outcome of this study would provide insight into the potential use of bioethanol mixture for generator engine applications and offer a pathway for future studies in different ratios of bioethanol to realize the significant benefits of generator engines for internal combustion engines.